Korelasi Empirik Kompresibilitas Tanah Permukaan Di Kota Pekanbaru - Wahyudi, Akmam; Satibi, Syawal; Nugroho, S A (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
preliminary study is needed to provide a general overview as well as the characteristics of the local soil conditions. So, we need an estimate of the local soil conditions and characteristics based on soil conditions and characteristics that have been known about the condition and characteristics, in order for a plan to be more efficient. Basically one soil parameter that is needed in the design of index compression (compression index) can be found using the correlation formula. This study aims to find the correlation formula recommendations more precise than some formula to use in calculating or predicting the value of index compression. Hand drill data obtained from the Laboratory of Soil Mechanics. To find a correlation formula recommendations, used some statistical parameters such as mean, standard deviation, and correlation index. Zoning analysis results showed that the thickness of the soft soil in general area of Pekanbaru has soft soil thickness was (a thickness of ten to fifteen feet). Zoning analysis results showed that the level of congestion ground Pekanbaru City area has a moderate level of congestion ground. From the evaluation of the correlation formula, based on static parameters obtained correlation formula recommendations azzous et al (1976) that Cc = 0:40 (E-0.25) and Cc = -0156 + + 0.00058wn sebgai 0.41eo correlation formula is best used in Pkenabaru.Keywords: soft ground, index compression, empirical correlations, the statistical parameters